Quantitative anatomy of the ulna’s shaft primary ossification center in the human fetus - Wiśniewski, Marcin (Surg Radiol Anat, 2018)
PURPOSE: There has been little information in the medical literature regarding the growing ulna in the human fetus, though such knowledge appears to be potentially useful in diagnosing skeletal dysplasias, characterized by a disrupted or completely halted growth of the fetus. Therefore, longitudinal measurements of long bones are extremely conducive in assessing both pregnancy and fetal anatomy. MATERIALS AND METHODS: Using methods of CT, digital-image analysis and statistics, the size of the ulna’s shaft primary ossification center in 48 (26 males and 22 females) spontaneously aborted human fetuses aged 17–30 weeks was studied. RESULTS: With no sex differences, the best fit growth dynamics for the ulna’s shaft primary ossification center was modeled by the following functions: y = − 8.476 + 1.561 × age ± 0.019 for its length, y = − 2.961 + 0.278 × age ± 0.016 for its proximal transverse diameter, y = – 0.587 + 0.107 × age ± 0.027 for its middle transverse diameter, y = − 2.865 + 0.226 × age ± 0.295 for its distal transverse diameter, y = − 50.758 + 0.251 × (age)(2) ± 0.016 for its projection surface area, and y = − 821.707 + 52.578 × age ± 0.018 ± 102.944 for its volume. CONCLUSIONS: The morphometric characteristics of the ulna’s shaft primary ossification center show neither sex nor bilateral differences. The ulna’s shaft primary ossification center grows linearly with respect to its length, transverse dimensions and volume, and follows a quadratic function with respect to its projection surface area. The obtained morphometric data of the ulna’s shaft primary ossification center is considered normative for respective prenatal weeks and may be of relevance in both the estimation of fetal ages and the diagnostic process of congenital defects.